Scanning near-field optical microscopy on rough surfaces: Applications in chemistry, biology, and medicine - Gerd Kaupp (International Journal of Photoenergy)
Shear-force apertureless scanning near-field optical microscopy (SNOM) with very sharp uncoated tapered waveguides relies on the unexpected enhancement of reflection in the shear-force gap. It is the technique for obtaining chemical (materials) contrast in the optical image of “real world” surfaces that are rough and very rough without topographical artifacts, and it is by far less complicated than other SNOM techniques that can only be used for very flat surfaces. The experimental use of the new photophysical effect is described. The applications of the new technique are manifold. Important mechanistic questions in solid-state chemistry (oxidation, diazotization, photodimerization, surface hydration, hydrolysis) are answered with respect to simultaneous AFM (atomic force microscopy) and detailed crystal packing. Prehistoric petrified bacteria and concomitant pyrite inclusions are also investigated with local RAMAN SNOM. Polymer beads and unstained biological objects (rabbit heart, shrimp eye) allow for nanoscopic analysis of cell organelles. Similarly, human teeth and a cancerous tissue are analyzed. Bladder cancer tissue is clearly differentiated from healthy tissue without staining and this opens a new highly promising diagnostic tool for precancer diagnosis. Industrial applications are demonstrated at the corrosion behavior of dental alloys (withdrawal of a widely used alloy, harmless substitutes), improvement of paper glazing, behavior of blood bags upon storage, quality assessment of metal particle preparations for surface enhanced RAMAN spectroscopy, and determination of diffusion coefficient and light fastness in textile fiber dyeing. The latter applications include fluorescence SNOM. Local fluorescence SNOM is also used in the study of partly aggregating dye nanoparticles within resin/varnish preparations. Unexpected new insights are obtained in all of the various fields that cannot be obtained by other techniques.